Development of the Diabetic Kidney Disease Mouse Model Culturing Embryos in α-Minimum Essential Medium In Vitro, and Feeding Barley Diet Attenuated the Pathology - Ishiyama, Shiori; Kimura, Mayu; Nakagawa, Takao; Fujimoto, Yuka; Uchimura, Kohei; Kishigami, Satoshi; Mochizuki, Kazuki (Frontiers in Endocrinology, 2021)
Diabetic kidney disease (DKD) is a critical complication associated with diabetes; however, there are only a few animal models that can be used to explore its pathogenesis. In the present study, we established a mouse model of DKD using a technique based on the Developmental Origins of Health and Disease theory, i.e., by manipulating the embryonic environment, and investigated whether a dietary intervention could ameliorate the model’s pathology. Two-cell embryos were cultured in vitro in α-minimum essential medium (MEM; MEM mice) or in standard potassium simplex-optimized medium (KSOM) as controls (KSOM mice) for 48 h, and the embryos were reintroduced into the mothers. The MEM and KSOM mice born were fed a high-fat, high-sugar diet for 58 days after they were 8 weeks old. Subsequently, half of the MEM mice and all KSOM mice were fed a diet containing rice powder (control diet), and the remaining MEM mice were fed a diet containing barley powder (barley diet) for 10 weeks. Glomerulosclerosis and pancreatic exhaustion were observed in MEM mice, but not in control KSOM mice. Renal arteriolar changes, including intimal thickening and increase in the rate of hyalinosis, were more pronounced in MEM mice fed a control diet than in KSOM mice. Immunostaining showed the higher expression of transforming growth factor beta (TGFB) in the proximal/distal renal tubules of MEM mice fed a control diet than in those of KSOM mice. Pathologies, such as glomerulosclerosis, renal arteriolar changes, and higher TGFB expression, were ameliorated by barley diet intake in MEM mice. These findings suggested that the MEM mouse is an effective DKD animal model that shows glomerulosclerosis and renal arteriolar changes, and barley intake can improve these pathologies in MEM mice.